(NvIZNX W MUZYKEs (NmONOGRAFIQ(B. (Nu^EBNIKs - (Nw(B.(Na(B.(NoSETROWAs ((NtA[KENTs Complex Print, 2025)
(NdANNAQ MONOGRAFIQ PREDSTAWLQET SOBOJ ISSLEDOWATELXSKIJ TRUD PO TWOR^ESTWU UZBEKSKOGO KOMPOZITORA SOWREMENNOSTI o(B.(Ni(B.(NsITNIKOWA(B.s
Keywords: (NMONOGRAFIQs